Rancang Bangun Pengujian Generator Pada Energi Ombak Di Pesisir Pantai - Firman - Yudianto; Fajar Annas Susanto (Universitas Islam Lamongan, 2020)
Indonesia is a country that has a very wide sea and has beaches that have waves on a small and large scale. Energy fulfillment is currently very necessary on a large scale.Given the problems and utilization, this research will conduct a generator test with a wave management system on the coast. The design of this generator testing will be carried out by designing mechanical manufacturing as well as hardware and software so that it can be used as a basic use to produce electrical energy with electric wave power which will greatly benefit the community around the coast.